Bias in Utility Assessments: Further Evidence and Explanations - Johnson, Eric J.; Schkade, David A. (Management Science, 1989)
Judgments about simple gambles, such as those used in utility assessment, can generate sizable and systematic bias. After Hershey and Schoemaker (Hershey, J. C., P. J. H. Schoemaker. 1985. Probability vs. certainty equivalence methods in utility measurement: Are they equivalent? Management Sci. 31 1213–1231.), we employ both the probability and certainty equivalence methods to explore bias. Our results show that: (1) the direction and degree of bias depend on characteristics of the assessment gamble such as the reference probability and the difference between outcomes, (2) presenting subjects with explicit anchors can change the size and direction of the bias, and (3) subjects using heuristic response strategies show significantly more bias than those using expectation strategies. We also discuss the status of possible explanations for the bias, in light of these new results, including PE mode reframing, random error, and anchoring and adjustment.